Assessing cold stress resilience in wild chickpea accessions using physiological, biochemical, and reproductive traits - Sarbjeet Kaur; Deeksha Padhiar; Mohar Singh; Swarup K. Parida; Uday C. Jha; Kamal Dev Sharma; P. V. Vara Prasad; Kadambot H. M. Siddique; Harsh Nayyar (Scientific Reports)
Abstract Domesticated chickpea (Cicer arietinum L.) exhibits high sensitivity to temperatures below 20/10 °C during its reproductive phase resulting in substantial loss of flowers, pods and crop yields. With the aim to add new sources of cold tolerance and elucidate mechanism of cold-tolerance in wild species of chickpea, the present study evaluated 36 wild accessions of three Cicer species (Cicer judaicum, Cicer pinnatifidum, Cicer reticulatum) at the reproductive stage for yield, and reproductive, physiological and biochemical traits under cold stress (15/7 °C) for two consecutive years. Cluster analysis based on yield-related traits such as pod number, seed weight, and total seed count categorized these accessions as cold-tolerant and cold-sensitive. Six C. judaicum accessions (ILWC 256, ICC 13852, ILWC 263, ILWC 20, ILWC 223, and ILWC 30) were tolerant to cold whereas the remaining ones were cold-sensitive. Under cold stress, cold-tolerant accessions exhibited lower impairment of physiological processes as compared to the cold-sensitive accessions e.g. lower tissue damage and electrolyte leakage, and higher chlorophyll content, carotenoid content, chlorophyll fluorescence, and leaf water content, thereby resulting in higher photosynthetic efficiency and carbohydrate accumulation in cold-tolerant accessions. At the biochemical level, the tolerant accessions demonstrated significantly higher amounts of cryoprotectants and enhanced activities of enzymatic and non-enzymatic antioxidants resulting in substantially lower levels of reactive oxygen species. Cold-tolerant accessions also accumulated more proline and trehalose compared to their sensitive counterparts. Slight disruptions in physiological processes, low oxidative stress and accumulation of cryoprotectants under cold stress were associated with higher pollen viability, pollen germination, pollen load, ovule receptivity, pod set, number of pods and seed yield in cold-tolerant accessions while opposite was true for cold-sensitive accessions. The wild chickpea accessions exhibiting high seed yield under cold stress are promising candidates for breeding programs aimed at cold tolerance.